PREPOSISI DALAM ALBUM â€œTAKE OFF YOUR PANTS AND JACKETâ€ - WERUPANGKEY, GEORGE CHRIONI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT This research entitled â€œPreposition in Album Take Off Your Pants and Jacket by Blink 182â€ is written to classify and analyze the form as well as the function of the preposition found in the Album.Â  The writer uses a theory from Aarts and Aarts (1982) to classify the forms of preposition and analyze the function. The method used in this research is descriptive method, and the data were taken from the Album by Blink 182. The result of this research shows that in the album Take Off Your Pants And Jacket there are several forms and function of preposition in prepositional phrase. The forms are simple and complex preposition. The function of preposition in prepositional phrase refer to, preposition in prepositional phrase as prepositional constituents, preposition in prepositional phrase as postmodifier noun phrase and adjective phrase, and preposition in prepositional phrase as prepositional complement. Key Words: English Preposition, Forms and Function, Take Off Your Pants And Jacket